Anemia in Young Women in Environment III Ladang Bambu Village, Medan Tuntungan District in 2020 - Dwi Ris Hasanah; Helena Fransysca (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to increase the knowledge and insight of adolescents about the risk of anemia, so that adolescents know how to manage nutritional coverage during their teenage years. Explaining to adolescents about what happens when during adolescence, nutritional patterns are not fulfilled, such as malnutrition, obesity, and anemia. Increase the knowledge of young women about nutrition and increase the knowledge of young women about anemia. The types and forms of activities of this activity are providing material to adolescents about anemia, namely, understanding, criteria for anemia, distribution of anemia, symptoms of anemia, and ways to overcome anemia in adolescents. To achieve the objectives of the above activities, activities were carried out including providing material to adolescents about anemia, namely, understanding, criteria for anemia, distribution of anemia, symptoms of anemia, and ways to overcome anemia in adolescents.